Terra, Trabalho e Escola: a luta do MST por uma educação do/no campo na Paraíba - Oliveira, Mara Edilara Batista de (2010)
In seeking to contribute, through research, in building a quality education for rural schools, we presented the conditions of modern education (2010) from different areas of rural Agrarian Reform Settlements in Paraiba for, from your analysis, construct ways of overcoming the reality challenged. Our premise is that there is a mismatch history educational / space of families who live and work in the field and there are also ways of organizing the working class who struggle for autonomy. " Given this, our research goal is to analyze the process of territorialization of the Movement of Landless Workers (MST) by education / field in the state, as the expression of one of these forms of class organization. The current reality in schools in the MST settlements in state history is a reflection of the educational conditions that have been denied the families of rural workers. The struggles of peasants and workers in Paraiba are part of its historical process of territorial formation. We highlight the decades of 1940-50 as an important moment in the peasant organization in the form of alloys. Peasant leagues organized rural workers and peasants dispossessed of their land rights, claimed the return to them and better working conditions. Even with the extermination of leagues in 1964, these workers organized in unions remained Rural and subsequently by the CPT. At the end of the 1980s and early 1990s, the MST began its first mobilization for the struggle for land in the state, and since its occupation first raised the banner of education in their territories. Claimed is not yet any one school but a school that rescued the history and culture of peasants and landless workers. Currently the 299 projects of rural Paraiba only 37 wins were the organization of the MST and those only 10 have 37 schools. The dynamics and meaning of these 10 schools for the MST struggle is our object of study. Operating conditions, infrastructure, political and pedagogical training, many times far from the ideals of the movement, lack of autonomy from the official teaching and understanding of the limits posed by an education aimed at the ruling class, are issues that we tried, but answer, in light of the contradictions of capitalist development in the field today.